Violence against Women and Girls : Lessons from South Asia - Solotaroff, Jennifer L.; Pande, Rohini Prabha (World Bank Group, Washington, DC, 2014)
This report documents the dynamics of violence against women in South Asia across the life cycle, from early childhood to old age. It explores the different types of violence that women may face throughout their lives, as well as the associated perpetrators (male and female), risk and protective factors for both victims and perpetrators, and interventions to address violence across all life cycle stages.